PROVERBS WITH THE COMPONENT “DWELLING” IN TATAR, RUSSIAN AND ENGLISH - Mukharlyamova, Liliya; Sulkarnayeva, Assiya (Revista Inclusiones, 2019)
Proverbs and sayings express a certain pattern of everyday or moral plan, which is based on certain concepts and areas of their interaction, information about the culture of the ethnos (characterize important moments of the history of the people, assess the meaning of life, and convey the customs and traditions of the speakers of a particular language). They reflect the features of relationships between people, the socio-historical context, and particularities of life, customs and traditions as well. In this article, an attempt is made to consider proverbs and sayings with the component “dwelling” in the Tatar, Russian and English languages. According to the analysis, the most frequent tokens expressing the semantics of “dwelling” were found: “oy” and “yort” – in the paroemiological fund of the Tatar language, in Russian it is the lexeme “house”, and in the proverbial fund of the English language it is the lexical unit “home”. Also, the proverbs were considered from the point of view of the expressed meanings, and it was determined that in all three difference-structured languages, there were paroemias with the values “home-residence”, “family”, “native land”, “human characteristics”, and “counseling-instruction”.